Innovating together: collaborating to impact performance - Slattery, K.; Crowcroft, S.; Coutts, A. J. (International Journal of Sports Physiology and Performance, 2021)
Sport scientists can impact sporting performance in several ways, through implementation of our research and when applying evidence-based practice in direct work with athletes. The impact of research is typically achieved through "slow and deliberate" work in the laboratory. In contrast, those operating in the field make their difference through "fast-paced" work in training and competition settings.1 While on the surface these roles appear dichotomous (ie, different skill sets, work deliverables, and performance expectations), there is great value when they combine. Important insights can be discovered from both the lab and in training and competition settings, and we believe that a "sweet spot of innovation" and collective benefit is achieved when the 2 meet. As an example, the role of lab-based research is to test the efficacy of interventions (eg, optimal methods for physiological adaptation, optimal learning strategies), while coaches and athletes test the intervention`s effectiveness in the real world. Undoubtedly, coaches and athletes benefit from the work of researchers, but there are great benefits to be achieved by working together to bridge the gap from research to practice. We have benefited greatly from the insightful feedback, opinions, and shared experiences of expert coaches and athletes. These insights have aided our understanding of contemporary training practices and provided new ideas for studies conducted in the lab. While it is common as scientists to think and act dichotomously, we believe that this both/and2 (as opposed to either/or) approach to problem solving is where the highest impact to sport performance can be made.